2020
DOI: 10.20944/preprints202012.0173.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 and Religion: Risks and Opportunities

Abstract: Culture, gender and religion are closely linked each other’s, profoundly affect the role of each person within the Society, and also affect the ability to access to the health resources. We are now living a worldwide crisis due to the SARS-CoV-2 pandemic. In order to appropriately tackle it, an alliance between science, politics and citizens is needed. In this article, we summarize current evidences of how religions can represent, on one hand, a risk moment for spreading the virus (in relation with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…The high seropositivity rate we observed among ultra‐orthodox Jews and Muslims contributed to the total seroprevalence rate found in this study. Previous studies have described how religious affiliation and communal ceremonies may have influenced SARS‐CoV‐2 transmission 19 . We also found that a larger family size was associated with seropositivity and this may provide another explanation for the high seroprevalence rate in this group.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The high seropositivity rate we observed among ultra‐orthodox Jews and Muslims contributed to the total seroprevalence rate found in this study. Previous studies have described how religious affiliation and communal ceremonies may have influenced SARS‐CoV‐2 transmission 19 . We also found that a larger family size was associated with seropositivity and this may provide another explanation for the high seroprevalence rate in this group.…”
Section: Discussionsupporting
confidence: 72%
“…Previous studies have described how religious affiliation and communal ceremonies may have influenced SARS-CoV-2 transmission. 19 We also found that a larger family size was associated with seropositivity and this may provide another explanation for the high seroprevalence rate in this group.…”
Section: Discussionsupporting
confidence: 61%
“…The keuchik obligated them to self-isolation with gampong's responsibility [9]. As seen in the above finding, Buonsenso et al [10] consider traditional concepts link religions with disease, since these concepts affect the responses of some categories of believers when in time of health crisis.…”
Section: Resultsmentioning
confidence: 99%